Sphingosine-1-Phosphate Signaling in Ischemic Stroke: From Bench to Bedside and Beyond - Zhang, Shuo-Qi; Xiao, Jun; Chen, Man; Zhou, Luo-Qi; Shang, Ke; Qin, Chuan; Tian, Dai-Shi (Frontiers in Cellular Neuroscience, 2021)
Sphingosine-1-phosphate (S1P) signaling is being increasingly recognized as a strong modulator of immune cell migration and endothelial function. Fingolimod and other S1P modulators in ischemic stroke treatment have shown promise in emerging experimental models and small-scale clinical trials. In this article, we will review the current knowledge of the role of S1P signaling in brain ischemia from the aspects of inflammation and immune interventions, sustaining endothelial functions, regulation of blood-brain barrier integrity, and functional recovery. We will then discuss the current and future therapeutic perspectives of targeting S1P for the treatment of ischemic stroke. Mechanism studies would help to bridge the gap between preclinical studies and clinical practice. Future success of bench-to-bedside translation shall be based on in depth understanding of S1P signaling during stroke and on the ability to have a fine temporal and spatial regulation of the signal pathway.